2012
DOI: 10.1097/acm.0b013e31824d4540
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bipolar Disorder and Schizophrenia in Houston Outreach Medicine, Education, and Social Services (HOMES) Clinic Patients

Abstract: The high prevalence of these mental illnesses combined with the increased burden of medical comorbidity among HOMES Clinic patients has implications for student-managed free clinics, which often operate on limited budgets. Strategies for providing care for these patients in this setting include integrated care, street medicine, and case management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“… 21 , 30 , 54 Other concepts that were used interchangeably with student-run included student-created ; student-developed , student-directed , student-driven , student-initiated , student-managed , student-operated , student-organized , student nurse-delivered , student pharmacist-led , student pharmacist-run , and student-volunteer . 6 , 7 , 29 , 55 - 63 In some cases, more than one term was used interchangeably within the same article, such as student-run and student-led . 6 , 62 - 67 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 21 , 30 , 54 Other concepts that were used interchangeably with student-run included student-created ; student-developed , student-directed , student-driven , student-initiated , student-managed , student-operated , student-organized , student nurse-delivered , student pharmacist-led , student pharmacist-run , and student-volunteer . 6 , 7 , 29 , 55 - 63 In some cases, more than one term was used interchangeably within the same article, such as student-run and student-led . 6 , 62 - 67 …”
Section: Resultsmentioning
confidence: 99%
“… 6 , 7 , 29 , 55 - 63 In some cases, more than one term was used interchangeably within the same article, such as student-run and student-led . 6 , 62 - 67 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis has concluded that reduced new depressive episodes may be achieved by long-term antidepressant treatment with no significantly increased risk of new manic/hypomanic episodes in BD (Liu et al, 2017). While SZ and BD remain highly prevalent in homeless people (Ayano et al, 2019;Welsh et al, 2012), little is known about MDD in this specific population, its prevalence and the effectiveness of psychotropic drugs. Additional factors including alcohol and substance use disorders that are highly prevalent in homeless subjects may also play a major role in depression diagnosis and remission under treatment (Lim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%